The winding road to platelet α-granules - Ambrosio, Andrea L.; Di Pietro, Santiago M. (Frontiers in Cell and Developmental Biology, 2025)
Platelets are anucleate cellular fragments derived from megakaryocytes (MKs) and α-granules constitute their most numerous membrane-bound compartments. These granules play a role in platelet aggregation to form a hemostatic plug but also contain numerous cargo proteins with key functions in angiogenesis, inflammation, wound healing and cancer. Human genetic disorders that cause deficiencies in the biogenesis of platelet α-granules manifest with prolonged bleeding. The initial studies on platelets and MKs from these patients provided a first glimpse into the biosynthesis of α-granules as a membrane trafficking problem. Significant progress in the field has been made in recent years in part due to the creation of iPSC-derived megakaryocytic cells capable of releasing functional platelets, thus overcoming the limitations of working with primary MKs. The emerging model indicates that sorting and recycling endosomes are key intermediate stations traversed by α-granule cargo on their way to the α-granule. Here we describe the different trafficking pathways used by α-granule proteins and elaborate on their commonalities. Similar to other lysosome-related organelles, most of the proteins involved in the biogenesis of α-granules are ubiquitously expressed and we discuss NBEAL2 as a factor highly expressed in MKs that likely diverts this machinery to make α-granules. Importantly, understanding the trafficking pathways involved in the making of the α-granule has an impact not only on platelet biology but may also illuminate the broader lysosome-related organelle field.